Charging the Rhino - Jacobovici, Simcha (Associated Producers Ltd., 2007)
Verzio FF Submission The film is a deeply personal exploration into the life of a Romanian family's history. Rounded up with relatives for mass execution in 1941, the director's father was shot, yet miraculously survived with a bullet lodged near his heart. His cousin suffered an even more bizarre fate: he survived the war but was forced to star in a Communist propaganda film. An account of the Romanian Jewish community’s suffering during WWII.